Investigating acute care physical therapy in general medicine: a retrospective analysis of utilization and effectiveness. - Crick Jr, James P.; Alain, Gabriel N.; Meirelles, Cristiane; Gehrig, Marka; Juckett, Lisa; Quatman, Carmen; Quatman-Yates, Catherine (Physiotherapy Theory & Practice, 2026)
Background: Physical therapy (PT) has been associated with improved patient- and system- outcomes for hospitalized patients. However, significant variation exists in PT delivery to general medicine patients, and there has been little research exploring the utilization and effectiveness of PT in this population. Purpose: The purpose of this study is to investigate the utilization and effectiveness of PT for acutely hospitalized general medicine patients, focusing on the relationship between PT minutes per day provided and patient functional improvement and discharge disposition. Methods: This retrospective observational cohort study analyzed clinical data from 7693 patients admitted to an urban academic medical center between July 2021 and December 2023. Patients included were at least 18 years old, discharged alive, and received at least two PT visits. The primary predictor variable was minutes per day of PT provided. The primary outcome was functional improvement, measured by the Activity Measure for Post-Acute Care (AM-PAC) Basic Mobility "six-clicks" score. The secondary outcome was discharge to home. Multivariable logistic regression models were used to estimate adjusted odds ratios (aOR) for functional improvement and discharge disposition. Results: Each 10-minute increase in PT minutes per day provided positively associated with functional improvement (aOR = 1.16 per 10-minute increase, 95% CI 1.07–1.25, p <.0001) and discharge to home (aOR = 1.22 per 10-minute increase, 95% CI 1.13–1.31, p <.0001). Higher daily PT thresholds showed increasing adjusted probabilities of functional improvement and discharge home, though gains in functional improvement plateaued beyond 30 minutes per day. Conclusion: Increased daily PT was associated with greater functional improvement and higher likelihood of discharge to home. These results support more intentional PT resource allocation and suggest that identifying clinically meaningful treatment thresholds may help guide therapist decision-making.